PENGGUNAAN OIL BACTER, ENDOMIKORIZA DALAM FITOREMEDIASI OILY SLUDGE DENGAN TANAMAN SENGON (PARASERIANTHES FALCATARIA L. NIELSEN) TERHADAP BIOSURFAKTAN DAN TOTAL PETROLEUM HYDROCARBON (TPH) - Nia Rossiana; Titin Supriatun; Dadan Sumiarsa (JURNAL ISTEK, 2012)
This research have been done onusingwild-typebacteriaand endomycchorhiza; oil bacter1 (Pseudomonas sp., Alcaligenessp., Flavobacteriumsp.,), Oilbacter2 (Bacillus megaterium, Alcaligenessp., Flavobacteriumsp.)and endomycchorhiza biounpadin oily sludge phytoremediationdose30%, 35%withplantsengon(Paraserianthes falcatariaL.Nielsen). The study was conductedwithan experimental methoduse a Completely RandomizedDesign(CRD) with 4combinationbetween the consortiumof bacteriain different doses with 3replications.The mediumused is amixture ofoily sludgewith soilandsandin the ratio2:1. Mediumiscompostedfor 1month, then plantedsengoninoculated endomycchorhiza aged1 monthand leftfor 8months. The parametersanalyzedwere:biosurfactantproduction, oil content/TPH(Total Petroleumhydrocarbon(%),the population of bacteria/TPC(Total PlateCount) (CFU /colonyformingunits), pH, humidity(%), infectionendomyccorhizapercentage(%). The resultsupto 8monthsshowedthat thecombination of consortiumof oilbacter 1(Pseudomonas sp., Alcaligenessp., Flavobacteriumsp.,)dose of35% oily sludgeproducedbiosurfactant0.332g/L, decrease ofTPH 37.09%, endomyccorhizainfectionin plantssengon26.67% -36.67%, population of bacteria 2.67x 106CFU, pH ofthe mediumfrom 5.1 to 6.3and70-83% humidity of medium.